Exploration and Identification of Rice Entomopathogens (Oryza sativa L.) Ogan Komering Ilir District - Haperindah Nunilahwati; Dewi Meidalima; Yani Purwanti; Laili Nisfuriah; Chuzaimah (Biological Environment and Pollution, 2022)
Entomopathogenic fungi are biological agents that play a very important role in suppressing or regulating pest populations in agricultural ecosystems. This study aims to explore and identify, as well as determine the ability of entomopathogenic infections from lowland rice (Oryza sativa L.) from Ogan Komering Ilir Regency. This research was conducted in the Pest and Plant Diseases Laboratory, Faculty of Agriculture, the University of Palembang from February to May 2022. The study used a Completely Randomized Design (CRD) method consisting of 5 treatments, namely PS1 = mortality of bait insects 3 days after infestation (hsi), PS2 = bait insect mortality 6 dsi, PS3 = bait insect mortality 9 dsi, PS4 = bait insect mortality 12 dsi, PS5 = bait insect mortality 15 dsi and 5 replicates. The results of this study concluded that the entomopathogenic fungus found in lowland rice (O. sativa L) from Ogan Komering Ilir Regency was Beauveriabassiana and had the ability to infect the highest bait insect mortality on day 9 after infestation.